IRS-assisted access link-based multihop THz communication - Sharma, Shubha (2024)
This paper proposes an amplify-and-forward (AF)- based multihop THz backhaul communication integrated with an access THz link. The access link is assisted with an intel- ligent reflecting surfaces (IRS) with an aim to deal with the impediments in THz communication environment. The statistical analysis is presented by deriving the probability density function (PDF) and cumulative distribution function (CDF) of the in- stantaneous signal-to-noise ratio (SNR) for the proposed system. The combined effect of path loss, atmospheric attenuation, and generalized fading is considered for modelling the THz channel. Furthermore, with the aid of PDF and CDF statistics, we propose the exact expressions for outage probability and develop asymptotic analysis in high SNR regime. The simulations are presented to validate the exact analysis and to study various design aspects for the proposed system.